TINGKAT KESUBURAN PERAIRAN BERDASARKAN KELIMPAHAN FITOPLANKTON DI DANAU BATUR, KINTAMANI, BALI - Sidaningrat, I Gusti Ayu Novie; Arthana, I Wayan; Suryaningtyas, Endang Wulandari (Metamorfosa: Journal of Biological Sciences, 2018)
Batur Lake is the largest lake in Bali, located in ??Kintamani, Bangli. Batur Lake is located at 1,050 meters above sea level (asl) which is geographically located in a position of 115022'42,3"-115025'33,0" East Latitude and 8013'24,0"-8017'13,3" South Latitude. The water surface area of Batur Lake is of ??16.05 km 2 with a volume of 815.38 million meters 3 and an average depth of 50.8 meters. The catching area is covering 105.35 km 2 , and other activities around Batur Lake are agricultural (49.35%), cultivation of floating net cage, settlements (2.22%), tourism activities, and dock. Those activities may increase nutrient input into waters that affect the productivity of waters. The aim of this research was to determine the abundance of phytoplankton that can be used as an indicator of productivity of waters in Batur Lake. The result of plankton community was supported by the diversity of phytoplankton as many as 16 species of 4 phylum. The abundance value of phytoplankton ranged between 2,686-2,983 individuals/Liter respectively which belongs to the mesotrophic waters (moderate waters fertility). The range of water quality parameters of temperature was 24.9-25.6 0 C; pH 9.02-9.06; DO 4.4-5.0 mg/L; brightness 119.1-138.4 cm; nitrate 0.452-0.598 mg/L; and phosphate 0.332-0.488 mg/L.